Dampak Implementasi Standar Operasional Prosedur dalam Meningkatkan Kinerja Karyawan di Restoran Chatter Lounge Gumaya Tower Semarang - Melyta Ayu Dwi Prastiwi; Jasanta Peranginangin; Denny Asmara (Tamasya : Jurnal Pariwisata Indonesia, 2025)
This study aims to examine and analyze how the implementation of Standard Operating Procedures (SOP) impacts employee performance improvement at Chatter Lounge Restaurant, Gumaya Tower Semarang. The background of this research stems from initial observations and interviews that revealed inconsistencies in SOP implementation, particularly in aspects of grooming and staff attitudes toward guests. A qualitative descriptive method with a case study approach was employed to gain a comprehensive understanding of the phenomenon. Data were collected through in-depth interviews with four key informants, direct observations of operational activities, and digital documentation related to SOP practices. The data analysis followed the interactive model of Miles and Huberman, which includes three main stages: data reduction, data display, and conclusion drawing. The findings indicate that SOP implementation positively contributes to enhancing employee discipline, time efficiency, and accuracy in following service procedures, leading to a more standardized service quality. Nevertheless, the implementation is not yet fully optimal as several employees lack a comprehensive understanding of SOP content. Inhibiting factors include limited advanced training opportunities, one-way briefings that restrict interactive communication, and the absence of a performance-based reward system to motivate staff. The study highlights that while SOPs serve as a crucial guideline to improve consistency and professionalism, their effectiveness depends heavily on continuous reinforcement and employee engagement. Therefore, it is recommended that the restaurant management strengthen SOP implementation through ongoing training, more participatory internal communication, and the establishment of performance-based reward mechanisms to maximize employee motivation, ensure service excellence, and ultimately enhance guest satisfaction.